Sustainable information technology practice in libraries - Ayinla, B.A.; Aramide, K.A. (IGI Global, 2023)
Information technology is a crucial tool required for the growth of all sectors in any nation. Undoubtedly, its application in libraries contributes significantly to meeting people’s information needs since libraries are essential in providing information services to information seekers. Thus, a well-organized library should have sustained information technology to assist in providing correct and timely services to its patrons. This chapter used current and relevant research findings and papers to explain various economic and social sustainability issues and challenges confronting IT adoption and practices in libraries. Similarly, it used recent research in cloud computing to explain some environmental sustainability issues related to information technology in libraries.